Estudio de productividad en la instalación de paredes livianas y repello en paredes de concreto armado del Nuevo Edificio de Residencias del TEC - Vásquez-Cubero, Karol Susana (Instituto Tecnológico de Costa Rica, 2016)
The research aims, collect reliable data from the Costa Rican construction, through the study methodology of work and to generate a database that can be used for the benefit of the construction industry, the study takes place in the headquarters of the Tecnológico de Costa Rica, the building of student residences for the purpose of measuring the productivity of constructive activities, which were selected according to the progress of the work. The results of productivity serve the engineering office to generate a database of projects administered by the institution, and improve the calculation of budgets and work times. The productivity of the installation of light walls was 46.40% and productivity in plaster reinforced concrete walls 50, 51%. Another objective was to calculate the percentage of residues that both activities Productivity, construction, construction activities, light walls, plastering, work study.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2016.
Keywords: Crew Balance; Mano de obra; Maquinaria; Productividad; Work Sampling